2.5D constructs for characterizing phase separated polymer blend surface morphology in tissue engineering scaffolds1. Issue 5 (27th November 2012) - Marszalek, Jolanta E.; Simon, Carl G.; Thodeti, Charles; Adapala, Ravi Kumar; Murthy, Ananth; Karim, Alamgir
Abstract: Previously, we used 2D films to identify an annealed PCL‐PDLLA phase‐separated blend morphology which provided nanoscale surface texture and patterning that stimulated osteoblast differentiation. In order to translate these 2D surface nanopatterning effects to the walls of 3D salt‐leached scaffolds, the blend phase morphology of scaffold walls must be characterized. For salt‐leached scaffolds, NaCl is used as a porogen, which may affect phase separation in PCL‐PDLLA blends. However, it is not possible to characterize the surface blend morphology of 3D scaffold walls using standard approaches such as AFM or optical microscopy, since scaffolds are too rough for AFM and do not transmit light for optical microscopy. We introduce a 2.5D approach that mimics the processing conditions of 3D salt‐leached scaffolds, but has a geometry amenable to surface characterization by AFM and optical microscopy. For the 2.5D approach, PCL‐PDLLA blend films were covered with NaCl crystals prior to annealing. The presence of NaCl significantly influenced blend morphology in PCL‐PDLLA 2.5D constructs causing increased surface roughness, higher percent PCL area on the surface and a smaller PCL domain size. During cell culture on 2.5D constructs, osteoblast (MC3T3‐E1) and dermal endothelial cell (MDEC) adhesion were enhanced on PCL‐PDLLA blends that were annealed with NaCl while chondrogenic cell (ATDC5) adhesion was diminished. This work introduces a 2.5D approach that mimicked 3D salt‐leached scaffold processing, but enabled characterization of scaffold surface properties by AFM and light microscopy, to demonstrate that the presence of NaCl during annealing strongly influenced polymer blend surface morphology and cell adhesion. Published 2012 Wiley Periodicals, Inc. † J Biomed Mater Res Part A, 2013.